Composition, ecology and conservation of the south-Iberian serpentine flora in the context of the Mediterranean basin. - Pérez-Latorre, Andrés Vicente; Hidalgo-Triana, Noelia; Cabezudo-Artero, Baltasar (CSIC, 2013)
Peridotite outcrops have special lithological (serpentine) and soil characteristics; they also support an unique flora and vegetation “that clearly differ from that of other soil types. One of the most important peridotite outcrops in the Western Mediterranean Basin is located in Sierra Bermeja (Andalusia, Spain). The establishment of a complete ecological-floristic checklist of serpentinophytes in this area, and a comparison with other serpentine-endemic floras in the Mediterranean Basin, is essential for the assessment, management and conservation of these special areas. The recognition of serpentinophytes was made following six criteria used for floras inhabiting special substrata,. The list of species exclusively or partially found on peridotite comprises 27 taxa with a variable degree of serpentinophily: obligate serpentinophytes (obligate endemics), preferential serpentinophytes (populations located mainly on serpentine) and subserpentinophytes (with some populations located on magnesium-rich substrata). As observed in other Mediterranean outcrops, the number of obligate serpentinophytes increases with the area of the outcrop, and the genera Alyssum, Arenaria, Armeria, Centaurea and Silene were the most frequent. Most of the studied serpentinophytes, except for a few xerothermophilous taxa, present a wide bioclimatic (altitudinal) range and grow in shrublands and pastures in rocky places with shallow soils. As many as 56% of the serpentinophytes are threatened and, among obligate serpentinophytes, 45% are categorized as critically endangered or endangered, emphasizing the need for urgent conservation measures on the species and their habitats Based on this checklist, more detailed studies may focus on serpentinophytes for their particular physiology, adaptive traits, functional types, phenology and applications.
Keywords: Flora - Mediterráneo (Región); Plantas serpentinícolas - Mediterráneo (Región); Mediterranean flora; Serpentinophytes; Peridotite rocks; Conservation; Ecology; Management